Direct liquefaction of Mukah Balingian low rank Malaysian coal using water-tetralin mixture at supercritical state / Zaidi Ab Ghani - Ab Ghani, Zaidi (2010)
Direct liquefaction on untreated Mukah Balingian (MB) coal using water-tetralin mixture was successfully performed in batch-wise reactor system, carried out at temperatures of 375 - 450°C and under pressure up to 22 MPa. The coal conversion and oil+gas yield obtained at optimum conditions of 450°C and 70:30 tetralin to water ratio, 22 MPa, 30 min reaction time, 1:10 coal-to-solvent ratio and with 500 rpm stirring rate, were 70.6 % and 66.1 % respectively. It was observed that heat plays an important role in comparison to pressure in contributing to high coal conversion and oil+gas yield, and these results are well correlated with the high content of reactive macerals. The addition of tetralin to water increased the coal conversion and oil+gas yield by the stabilization of radical fragments and inhibition of radical recombination. In this study, the application of response surface methodology (RSM) and central composite rotatable design (CCRD) for modeling the influence of reaction temperature and solvent mixed ratios on the liquefaction of MB coal. Predicted values were found to be in good agreement with the experimental values (R2 values of 0.9989 and 0.9931 for coal conversion and oil+gas yield respectively).This study has shown that the CCRD and RSM could efficiently be applied for the modeling liquefaction of coal and it is economical way of obtaining the maximum amount of information in a short period of time and with the fewest number of experiments. In this study, microwave irradiation pretreatment was applied on MB coal prior to coal conversion and products yield. The coal conversion and oil+gas yield obtained increased up to 8 - 16 % and 10 - 19 %, respectively. Inherent moisture in coal was found to be the determining factor in increasing coal conversion and oil+gas yield by absorbing the microwave energy in order formation of cracks and fissures in coal microstructure that enhanced the coal-to-solvent interaction, and the weakened C-C bonds, respectively.